Discovery of Novel Doxorubicin Metabolites in MCF7 Doxorubicin-Resistant Cells - Wang, Xu; Hui, Renjie; Chen, Yun; Wang, Wentao; Chen, Yujiao; Gong, Xiaohai; Jin, Jian (Frontiers in Pharmacology, 2019)
Pharmacokinetics describes the absorption, distribution as well as the effects and excretion of the metabolites of the drugs in the body, but little is known about drug metabolism in target cells. Doxorubicin (DOX) is a member of anthracycline family and commonly used as an anti-tumor agent. Doxorubicin is metabolized to a variety of metabolites in vivo, which has been shown to be associated with cardiotoxicity. We speculate that metabolic processes are also present in tumor cells. A LC-MS/MS method was developed to detect intracellular metabolites. Drug resistant tumor cells with high drug stress tolerance and metabolically active are suitable as materials for this study. Our results show difference in drug metabolites between the wild type and drug-resistant cells. Three novel doxorubicin metabolites were discovered after the LC-MS/MS analysis. All these metabolites and their profiles of metabolites are totally different from that in liver or kidney in vivo. Our results suggest that tumor cells and drug-resistant tumor cells may have a unique drug metabolism pathway for doxorubicin.